PROSEDUR DAN MEKANISME PELAPORAN PPN OLEH WAJIB PAJAK BADANDI KANTOR KONSULTAN XYZ - Trisya Shafa Febriana (Universitas Prof.Hazairin,SH Bengkulu, 2025)
Value Added Tax (VAT) is an important source of state revenue that plays a strategic role in supporting national development. However, many corporate taxpayers still encounter difficulties in VAT reporting due to limited understanding of regulations, administrative errors, and technical challenges in using digital tax systems such as eFaktur and Coretax. This study aims to analyze the procedures and mechanisms of VAT reporting for corporate taxpayers at a tax consulting firm in Sidoarjo, East Java. Using a qualitative descriptive case study approach, data were collected through participatory observation, in-depth interviews, and document analysis. The VAT reporting process includes stages of document collection, verification, data recapitalization, reconciliation, and submission of the VAT Periodic Tax Return (SPT Masa PPN) electronically. The findings show that the consulting firm has implemented a structured reporting workflow supported by internal controls such as Document Internal Monitoring (DIM), standardized working papers, and peer review to ensure accuracy and compliance. However, challenges remain, including delays in the submission of client documents, limited human resources, reliance on manual Excel processing, and frequently changing tax regulations. Strategies implemented include proactive communication with clients, the use of standardized Excel templates with data validation, and staff competency development through training.